On the Shoulders of Giants: Benefits of Participating in a Dialogic Professional Development Program for In-Service Teachers - Rodriguez, Jose A.; Condom-Bosch, Jose Luis; Ruiz, Laura; Oliver, Esther (Frontiers in Psychology, 2020)
This study explores the impact of a seminar on teacher's professional development, concretely in self-efficacy, and argumentative skills. Drawing on scientific readings, a group of teachers meeting once a month at the seminar called "On the Shoulders of Giants" critically discuss educational theory, which transforms their everyday practices within the school. A survey using a questionnaire was conducted, to collect the data. Results show that teachers' involvement in dialogic-based training positively impacts their ability to address current school problems, reporting that they transfer their new knowledge to their work. The effectiveness of their' practices increases and, as a consequence, their students' learning also improves.